2022
DOI: 10.3389/fresc.2022.780736
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Pulmonary Rehabilitation for Chronic Obstructive Pulmonary Disease in the Home and Community Setting: A Rapid Review

Abstract: This paper presents a rapid review of the literature for the components, benefits, barriers, and facilitators of pulmonary rehabilitation for chronic obstructive pulmonary disease (COPD) people in-home and community-based settings. seventy-six studies were included: 57 home-based pulmonary rehabilitation (HBPR) studies and 19 community-based pulmonary rehabilitation (CBPR) studies. The benefits of HBPR on exercise capacity and health-related quality of life were observed in one-group studies, studies comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…Nevertheless, most research into COPD hospitalization prevention is still focused on treatment in a hospital ( 17 ). In line with other studies, our findings call for increased attention to and capacity for treating COPD patients outside the hospital system ( 55 57 ). In our study, the reimbursement data indicated that there was no increase in GP care despite the increased use of physiotherapy care.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, most research into COPD hospitalization prevention is still focused on treatment in a hospital ( 17 ). In line with other studies, our findings call for increased attention to and capacity for treating COPD patients outside the hospital system ( 55 57 ). In our study, the reimbursement data indicated that there was no increase in GP care despite the increased use of physiotherapy care.…”
Section: Discussionsupporting
confidence: 92%
“…The diversity of telerehabilitation delivery models also creates heterogeneity in programme components. This includes the type and amount of clinician supervision of exercise training, for example real-time supervision versus asynchronous supervision/oversight; individually prescribed and progressed exercise training or self-paced training; the nature and degree of communication between patients and healthcare professionals, for example two-way verbal communication through to patient-initiated asynchronous, written correspondence; the amount and complexity of equipment required for telerehabilitation delivery, for example fixed telephone versus internet-enabled device with or without videoconferencing capabilities; and minimal low cost or specialist exercise training equipment [46]. It is likely that the optimal delivery model for telerehabilitation may vary according to resources available and patient characteristics.…”
Section: Models and Evidence For Telerehabilitationmentioning
confidence: 99%
“…PR is the gate to reduce COPD symptoms, and to improve exercise capacity and overall quality of life [ 6 ]. However, COPD patients face difficulties in accessing traditional PR services, whether due to high costs, limited infrastructure, lack of interest, and, even if they start PR, there is generally a poor adherence rate to PR programmes [ 6 , 7 , 8 ]. A recent prospective multicentre cohort study found that only 1% of patients hospitalised with COPD exacerbation utilised PR after discharge, with no in-hospital interventions associated with increased PR use [ 9 ].…”
Section: Introductionmentioning
confidence: 99%